Research in Times of Crisis Research Methods in the Time of COVID-19. - Hill, Aaron D. (Research Methodology in Strategy and Management Ser., 2021)
Research Methodology in Strategy and Managementadvances understanding of the methods used to study organizations - including managers, strategies, and how firms succeed.